Draft Annual Plan 1984-85 Government of Bihar - Planning Commission (Planning Commission, 1984)
Bihar with an area of 1.74 lakh square kilometres constitutes 5.3 per cent of the total area of the country. Its population according to the 1981 Census is however 69.91 millions which accounts for 10.21 per cent of the total population of the country. The density of population is 402 persons per square kilometre which is also quite high as compared to the All-India average of 208 persons per sq. km. only. The State continues to remain predominantly rural with 87.5 per cent of its total population living in the countryside against the All-India average of 76.3 per cent according to the 1981 Census. Its economy also continues to be overwhelmingly dependent on agriculture, with 79.07 per cent of its total population earning their livelihood from cultivation either as cultivators or agricultural labourers.
Planning Department